Graphene-based materials for biotransistor application - Ng, Wei-Beng (2019)
A biomimetic cell membrane bioelectronic transistor consisting of a supported phospholipid bilayer atop chemical vapor deposition (CVD) graphene or solution processed reduced graphene oxide on titanium dioxide (TiO2) has been successfully demonstrated for biosensing application. For the first time, a unique bonding interaction between titanium and carbon atom on graphene oxide has been experimentally identified by X-ray Photoelectron Spectroscopy (XPS). The covalent interaction acts as a strong surface anchorage in facilitating uniform adhesion and near to ideal surface coverage of spin coated graphene oxide on titanium bearing substrate using the in-situ solid-liquid phase exfoliation method. The liquid gated Reduced Graphene Oxide (RGO) biotransistor is sensitive to environmental changes in ionic strength of liquid environment by shift in electrical output signals at a sensitivity level of ~0.030mA per millimolar at gate bias VG=-8V and 0.035mA per millimolar at drain bias VD=1V. Incorporation of a phospholipid membrane atop the RGO transformed the sensing transistor to a bioelectronic transistor capable of sensing attached biomolecules on functionalized lipid/RGO surface acting as pseudo gate bias which modulated the electrical signals output. Supported neutral and charged lipid membranes on RGO at active source-drain region were formed by solvent assisted lipid bilayer (SALB) formation. A modulation of transistor conductance induced by gate charges were observed by the measurement of transistor drain current. Based on the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC)/RGO biotransistor platform, a functional supported lipid bilayer (SLB) was demonstrated using biotin-streptavidin binding event. The quantification of biotin composition with respect to transistor drain current modulation was monitored which showed a linear relationship between the percentage of changes in drain current versus the percentage of biotin composition in the complex SLB. For instance, a 12% change in drain current was measured for a 1wt % biotinylated DOPC lipid complex membrane upon streptavidin binding. The results illustrated the potential of using lipid bilayer as an efficient biofunctionalization tool on graphene oxide as a highly versatile and sensitive biosensing platform for a variety of receptor-ligand binding events.